Social responsibility of business: a case study of grameen phone in bangladesh - Nimalathasan, B. (University of Jaffna, 2009)
The social responsibility of business organisations is getting increased attention in recent years, and a strong perception has developed among the business managers worldwide and that organisations need to be managed in a socially responsible way for economic viability and long term sustainability. Therefore, the social responsibility of businesses has become an important part of today’s business agenda. The paper aims to investigate the social responsibility of business: a case study of Grameen phone in Bangladesh and identify different Corporate Social Responsibility (CSR) activities of Grameen phone (GP). Secondary data collection methods were used to conduct the study. It can be concluded GP believe that sustainable development can only be achieved through long term economic growth and therefore, intended to deliver the best to the customers, business partners, stakeholders, employees and society by ‘being a partner in development.
Keywords: Social responsibility of business; Social performance; Business